Problemy wykorzystania mechanizmu czystego rozwoju w produkcji energii z odpadów - Ciechelska, Agnieszka (Problems of Using Clean Development Mechanism for Waste Energy Production, 2009)
The creation of international emissions of CO2 trading is the effect of Kioto Protocol's obligations connected with the reduction of greenhouse gases emission. The Protocol introduces 3 market mechanisms, namely the Kioto Mechanisms to achieve their emission reduction: - Emission Trading - ET, - Joint Implementation - JI, - Clean Development Mechanism - CDM. In CDM Annex I parties which have emission caps (developed countries), assist non-Annex parties which do not have emission caps (developing countries), to implement Project activities to reduce GHG emissions, and instead receive credit (certified emission reduction - CER). CER are based on emission reductions achieved by the Project activities and can be used by governments or private sector to achieve the Protocol targets. The waste sector is the one of the main sectors engagement in the CDM. CDM Project must be realized according to procedures. The aim of this article is the analysis of CDM Projects in waste sector: types and developing stage, countries-investors and countries-beneficiates. The article also describes the most popular problems connected with CDM waste projects
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 83, s. 212-223